BODY SHAMING DENGAN HARGA DIRI DAN MEKANISME KOPING REMAJA - Khoir, Fathul; Kardiatun, Tutur; Ultari, Cici; Parliani, Parliani; Hastuti, Lidia (Jurnal Keperawatan dan Kesehatan, 2021)
BODY SHAMING DENGAN HARGA DIRI DAN MEKANISME KOPING REMAJA Fathul Khoir, Tutur Kardiatun, Cici Ultari, Parliani, Lidia Hastuti STIK Muhammadiyah Pontianak khoir@stikmuhptk.ac.id Abstract Background: adolescents have experienced body shaming which causes changes in self-esteem that stimulate adaptive or maladaptive coping mechanisms. Objective: to determine the relationship between body shaming and self-esteem with coping mechanisms adolescents at SMAN 2 Mempawah Hilir. Methods: descriptive research with cross sectional correlation approach, total sampling technique amounted to 50 students. The instrument uses the body Shaming Checklist sheet, Rosenberg Self-Esteem Scale, and Ways Of Coping. Results: There is no relationship between body shaming and adolescent self-esteem at SMAN 2 Mempawah Hilir (p = 0.596), and there is no relationship between body shaming and coping mechanisms in adolescents at SMAN 2 Mempawah Hilir (p = 0.456). Conclusion: majority of adolescents in SMAN 2 Mempawah Hilir have high or positive self-esteem with adaptive coping mechanisms. Some teenagers stated that body shaming is a criticism to improve themselves, divert body shaming in a spiritual way, such as prayer being given patience, and being ignorant. Keywords: Body Shaming, Self-Esteem, Coping Mechanism